2022
DOI: 10.3390/ijerph19127093
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Housing Tenure Opportunities in the Social Integration of the Aging Pre-1970 Migrants in Beijing

Abstract: This study focuses on the social integration of the pre-1970 first-generation migrants in reformist China, who were born before the year 1970 while getting old in the destination cities. The pre-1970 first-generation migrants are not a homogeneous group but are composed of: (a) those over 45 years old and still working but facing age discrimination; and (b) the elderly granny as nanny assuming the domestic and child-care work for their sons or daughters in the destination cities. We conceptualized and re-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…In the traditional Chinese cultural and social environment, migrants make homeownership a vital goal for working and settlement in the host city. Zhu et al [78] demonstrated that housing tenure was conducive to enhancing the social integration of the ageing pre-1970 in Beijing. Housing purchases and improving urban integration of migrants can both enhance their sense of happiness [79].…”
mentioning
confidence: 99%
“…In the traditional Chinese cultural and social environment, migrants make homeownership a vital goal for working and settlement in the host city. Zhu et al [78] demonstrated that housing tenure was conducive to enhancing the social integration of the ageing pre-1970 in Beijing. Housing purchases and improving urban integration of migrants can both enhance their sense of happiness [79].…”
mentioning
confidence: 99%
“…Another in-depth research (Chen et al, 2023) found that urban village regeneration undermines social equity and causes social conflicts, negatively affecting migrant integration into the city. Moreover, a study (Zhu et al, 2022) on ageing migrants has proven that housing tenure matters and entitlement would be conducive to improving their integration.…”
Section: Neighbourhood and Migrant Integration In Chinamentioning
confidence: 99%
“…There are also some studies from China, where Liu & Dijst (2014), by analyzing three datasets, the 2000 Shanghai Census, the 2001 Shanghai Basic Facilities Census, and the Shanghai Digital Street Network database, found that the constraints of the Chinese household registration system caused residential segregation between local and the older floating population in Shanghai, i.e., local the older adults lived mostly in the city center, while mobile the older mostly live in the periphery of the city, which makes them have unequal access to various material and social resources, and ultimately produces significant happiness inequality. using data from the 2017 Beijing Migrants Dynamic Monitoring Survey (MDMS), Zhu et al (2022) found that housing tenure rights will help enhance the integration of the older floating population, thus improving their subjective wellbeing (SWB), such that those living in informal housing are more likely to perceive subjective well-being than those living in dormitory-style housing.…”
Section: Social Integration and Mental Health Of The Older Floating P...mentioning
confidence: 99%
“…The emergence of health problems among the older floating population in China is attributed to institutional constraints, language barriers, and maladjustment to the new environment. In contrast to the older floating population in Europe and the United States, who move for old age and caregiving purposes (Litwak & Longino, 1987;Longino & Bradley, 2003;Rosano & Di, 2022), the older floating population in China migrates mainly for caring for grandchildren, labor and employment, and old age (Sun, 2013;Zhu et al, 2022;Gu et al, 2022), with the lowest proportion of old-age care (refer to Figure 2 in the Appendix). The majority of the older floating population that migrated for labor employment are migrant workers in their early years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation